Penerapan Pursed Lip Breathing Berbasis Evidence-Based Nursing pada Pasien PPOK Eksaserbasi - Simanjuntak Machdalena; Hijaz Muhammad; Susilawati Susilawati; Hutasoit Ceryah Lys Mey (Rumah Sakit Ibnu Sina, Makassar, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease characterized by airflow limitation and impaired gas exchange, which often leads to dyspnea and decreased quality of life. Pursed Lip Breathing (PLB) is a non-pharmacological intervention based on Evidence-Based Nursing (EBN) that has been shown to improve ventilation and reduce dyspnea in patients with COPD. This case report aims to describe the implementation of Evidence-Based Nursing–based Pursed Lip Breathing in a patient with COPD. The method employed a case report design involving a patient with COPD exacerbation and impaired gas exchange; a comprehensive nursing assessment was conducted, including subjective and objective data, physical examination, and supporting diagnostic tests. The main nursing intervention was Pursed Lip Breathing, provided gradually according to the patient’s tolerance, along with airway management and oxygen therapy, and evaluated based on clinical outcomes. The results showed improvement in respiratory status indicated by reduced dyspnea, more stable respiratory rate, decreased adventitious breath sounds, improved ability to perform effective coughing, improved oxygen saturation, and the patient’s ability to perform PLB independently. In conclusion, Evidence-Based Nursing–based Pursed Lip Breathing is beneficial in improving respiratory status and reducing dyspnea and can be incorporated as part of comprehensive nursing care for patients with COPD.